Recent coastline changes of fan-deltas in the Western Gulf of Corinth, Central Greece - Perrou, Th.; Kaza, I.; Efthymiadis, V.; Karymbalis, E.; Chalkias, C. (Bulletin of the Geological Society of Greece, 2013)
This study deals with the assessment of recent shoreline change rates along the fandeltas of Finix, Tholopotamo, Lagadi, Meganitas, Selinous, Kerinitis, and Vouraikos streams by using GIS and Remote Sensing techniques. These Late Holocene fandeltas have been formed by high gradient braided streams that deposit their coarse sediment load along the southern coast (North Peloponnese) of the western Gulf of Corinth. For the purposes of the study a spatial database was constructed, organized and implemented consisting of analogue detailed (at the scale of 1:5000) topographic diagrams, and orthorectified aerial photos taken in 1945, 1996 and 2008. Comparisons of fan-deltas shoreline positions for the periods 1945 vs. 1996 and 1945 vs. 2008 were made and the segments of the coastline along the aprons of the fan-deltas which are subject to erosion accretion were defined. Coastal erosion is the main dominant geomorphic process along a significant part of the fan deltas coastline. The highest retreat rate value (2.44 m/yr for the period 1945-1996) was estimated for the Finix stream fan delta, about 150 m west of the river mouth, while the highest accretion rates since 1945 (3.10 and 3.00 m/yr) occurred at the mouths of Vouraikos and Selinous rivers respectively.